Biotech & pharma: unique business in history - Haloub, Radi (Henry Stewart Talks, 2025)
Historical pharma evolution, Drug safety, Medicines policy components, Biotech companies, Modern biotech definitions, Generic and branded pharma companies, Industry structure dynamic